let X be non empty set ; :: thesis: for a, b being Real
for f being PartFunc of X,REAL st f is nonnegative & a > 0 & b > 0 holds
(f to_power a) to_power b = f to_power (a * b)

let a, b be Real; :: thesis: for f being PartFunc of X,REAL st f is nonnegative & a > 0 & b > 0 holds
(f to_power a) to_power b = f to_power (a * b)

let f be PartFunc of X,REAL; :: thesis: ( f is nonnegative & a > 0 & b > 0 implies (f to_power a) to_power b = f to_power (a * b) )
assume A1: ( f is nonnegative & a > 0 & b > 0 ) ; :: thesis: (f to_power a) to_power b = f to_power (a * b)
A2: ( dom (f to_power a) = dom f & dom ((f to_power a) to_power b) = dom (f to_power a) & dom (f to_power (a * b)) = dom f ) by MESFUN6C:def 4;
for x being object st x in dom ((f to_power a) to_power b) holds
((f to_power a) to_power b) . x = (f to_power (a * b)) . x
proof
let x be object ; :: thesis: ( x in dom ((f to_power a) to_power b) implies ((f to_power a) to_power b) . x = (f to_power (a * b)) . x )
assume A3: x in dom ((f to_power a) to_power b) ; :: thesis: ((f to_power a) to_power b) . x = (f to_power (a * b)) . x
then A4: ((f to_power a) to_power b) . x = ((f to_power a) . x) to_power b by MESFUN6C:def 4
.= ((f . x) to_power a) to_power b by ;
A5: (f to_power (a * b)) . x = (f . x) to_power (a * b) by ;
then A6: ( f . x > 0 implies ((f to_power a) to_power b) . x = (f to_power (a * b)) . x ) by ;
now :: thesis: ( f . x = 0 implies ((f to_power a) to_power b) . x = (f to_power (a * b)) . x )
assume A7: f . x = 0 ; :: thesis: ((f to_power a) to_power b) . x = (f to_power (a * b)) . x
then ((f to_power a) to_power b) . x = 0 to_power b by ;
then ((f to_power a) to_power b) . x = 0 by ;
hence ((f to_power a) to_power b) . x = (f to_power (a * b)) . x by ; :: thesis: verum
end;
hence ((f to_power a) to_power b) . x = (f to_power (a * b)) . x by ; :: thesis: verum
end;
hence (f to_power a) to_power b = f to_power (a * b) by ; :: thesis: verum